2018
DOI: 10.3390/ijms19071919
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Vitamin D Receptor Gene (VDR) May Have an Impact on Acute Pancreatitis (AP) Development: A Prospective Study in Populations of AP Patients and Alcohol-Abuse Controls

Abstract: Vitamin D imbalance is suggested to be associated with the development of pancreatitis. Single nucleotide polymorphisms (SNPs), Apa-1, Bsm-1, Fok-1, and Taq-1, in the vitamin D receptor gene (VDR) are known in various diseases, but not yet in pancreatitis. The aim of this study was to explore possible associations of the four SNPs in the VDR receptor gene in a population of acute pancreatitis patients and alcohol-abuse controls, and to investigate the association with acute pancreatitis (AP) susceptibility. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
(71 reference statements)
3
12
0
Order By: Relevance
“…Also, the presence of the TT genotype was four times more frequent in the AP group (OR = 4.55; 95% CI: 1.69-12.20; P = .003) in comparison to the control group. 26 VDR signaling may be reduced or even activated dependent on the occurrence of specific single nucleotide polymorphism in AP similar to what has been described in the progression of some tumors. Vitamin D reduces oxidative stress through the induction of antioxidant activity by itself, and, importantly, oxidative damage has been implicated in acute pancreatitis initiation.…”
Section: Discussionsupporting
confidence: 61%
“…Also, the presence of the TT genotype was four times more frequent in the AP group (OR = 4.55; 95% CI: 1.69-12.20; P = .003) in comparison to the control group. 26 VDR signaling may be reduced or even activated dependent on the occurrence of specific single nucleotide polymorphism in AP similar to what has been described in the progression of some tumors. Vitamin D reduces oxidative stress through the induction of antioxidant activity by itself, and, importantly, oxidative damage has been implicated in acute pancreatitis initiation.…”
Section: Discussionsupporting
confidence: 61%
“…Our previous study indicated that oxidative stress and Nrf2/HO-1 pathway were dynamically changed in pancreatic tissue of AP mice and were the most significant at the peak of inflammatory response [16]. Many clinical studies and animal experiments also showed the role of oxidative stress and ROS generation in the pathophysiological response of AP, activation of Nrf2/HO-1 pathway, and reduction of ROS generation, which showed the protective effect against AP [33][34][35][36]. Additionally, after reanalyzing the sequencing results of relevant research [37], we found that HO-1 increased significantly in the AP mouse model induced by caerulein (3.38-fold change vs. normal, p = 0:0001), while other related genes including Keap1, NQO1, and GCLM had no significant changes.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the effects of the VDR SNPs were also investigated in acute pancreatitis (AP). It was found that a particular SNP (allele T in Taq 1) is almost three times more frequent in AP patents in comparison with alcohol-abuse controls [7]. Thus, it seems that alteration in vitamin D signaling through the presence of unique SNPs in the VDR gene may be associated with predisposition to certain pathologies.…”
Section: Vitamin D and Healthmentioning
confidence: 99%